Urban space Appropriation: a glimpse to the state of the art of environmental psychology (Mayéutica Revista Científica de Humanidades y Artes, 2014)
In the process of humankind psychological development, the existence of innumerable variables that link their continuity and evolution in the planet takes place, inevitably one of these variable is the environment, which grants an immediate contribution to well-being, harmony and their definitive permanency in the world; this article is aimed at thinking about the state of the art of environmental psychology by investigating its origins and evolution in the area of the discipline. As well as being aware of the concept of urban spaces appropriation from Korosec-Serfaty, 1976; Pol, 2002a; Vidal, Pol, Guàrdia and Peró, 2004 standpoints, who consider the link between people an public or private daily places, relating it to people’s behavior, that will allow us to think about ecological behavior and modernity.
Keywords: environmental psychology; urban space appropriation